2020
DOI: 10.26442/00403660.2020.02.000483
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal disorders in patients with irritable bowel syndrome

Abstract: Aim.To study the whole range of esophageal disorders in patients with irritable bowel syndrome (IBS) using high-tech methods. Materials and methods.102 IBS patients (47 males, mean age 40.8, diagnosis of IBS was established according to Rome III criteria) with esophageal symptoms (heartburn, belching, globus sensation and noncardiac chest pain) were examined in gastroenterology department. All patients underwent endoscopy, with biopsies if required, X-ray examination of upper gastrointestinal tract; 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Among the studies that reported the presence of GERD among IBS patients, pourhoseingholi et al reported the highest prevalence rate, being 74.7% GERD patients among 18,180 patients with IBS. 16 On the other hand, the lowest prevalence rate of patients with GERD among an IBS population was found to be 20.6%, however, the sample size was limited being 102 only as reported by Morozova et al 25 Another four studies have also reported the prevalence of GERD symptoms among patients with IBS. A large study by El Slahy et al reported that 66% of their 1489 IBS patients were diagnosed with GERD.…”
Section: Evidence Of Ibs and Gerd Overlapmentioning
confidence: 95%
See 3 more Smart Citations
“…Among the studies that reported the presence of GERD among IBS patients, pourhoseingholi et al reported the highest prevalence rate, being 74.7% GERD patients among 18,180 patients with IBS. 16 On the other hand, the lowest prevalence rate of patients with GERD among an IBS population was found to be 20.6%, however, the sample size was limited being 102 only as reported by Morozova et al 25 Another four studies have also reported the prevalence of GERD symptoms among patients with IBS. A large study by El Slahy et al reported that 66% of their 1489 IBS patients were diagnosed with GERD.…”
Section: Evidence Of Ibs and Gerd Overlapmentioning
confidence: 95%
“…1820 At baseline, three studies included patients with GERD, six included patients with IBS, while seven included patients with non-specified GERD or IBS to study the correlation as to their primary outcome. [15][16][17][18][21][22][23][24][25][26][27][28][29][30] Almost all studies were cross-sectional in design while only two studies were RCTs. 27,30 All of the studies were published between 2011 and 2020 as presented in Table 2, together with other baseline characteristics and outcomes.…”
Section: Included Studies Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations